Preparing Arabic Rhetoric Book In The Light Of Project-Based Learning/ إعداد كتاب علم المعاني على ضوء التعلم القائم على المشاريع - Yusuf, Enjang Burhanudin; Ainin, Moh. Ainin; Hamid, M. Abdul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The study was conducted to develop and evaluate the effectiveness of the teaching materials used for Ilm al Ma'ani based on Project Based Learning (PjBL) in the Arabic Language Department - The State Islamic University of Prof. K.H. Saifuddin Zuhri Purwokerto, Indonesia. This study used Research and Development (R and D) designed by Borg and Gall. The data was collected using interviews, observations, questionnaires, and tests. The data analysis techniques included descriptive qualitative data analysis and descriptive statistics. This study's product is a textbook with the characteristics of mind mapping, analysis models, and exercises in every chapter. The experts in Ilm al Ma'ani, Arabic language, and textbook design have validated the textbook. The results of the expert's validation and the students' opinions are excellent because the product improves the students' learning competence and academic performance. Using the teaching materials for PjBL-based Ilm al Ma'ani obtains effective results. The Normality Tests using SPPS show that the posttest average value of the students is higher than the pretest average value. It means that there is a significant increase in the average value.